Long-term impact of physical activity on the prevention of cognitive function decline: study protocol for an extended randomized controlled trial (PA Protect study) - Adamczak, Ada Maria; Jamka, Małgorzata; Kotecka, Klaudia; Makarewicz-Bukowska, Aleksandra; Brylak, Jan; Dzudzewicz, Anna; Geltz, Jakub; Mądry, Edyta; Nowak, Jan Krzysztof; Herzig, Karl-Heinz; Walkowiak, Jarosław (Journal of Medical Science, 2025)
The PA Protect study investigated the impact of increased daily physical activity on preventing cognitive decline, and maintaining healthy biomarker levels in individuals with mild cognitive impairment. Participants aged 50-70 years, selected based on their performance in the Montreal Cognitive Assessment test were enrolled in a double-blind randomized controlled trial and randomly assigned to either an active or passive group. The active group was instructed to achieve over 10,000 daily steps, while the passive group maintained usual activity levels. Preliminary findings revealed a positive influence of increased physical activity on cognitive function, with significant differences observed between the two groups in selected cognitive tests. Building on these results, this study extends the PA Protect trial for an additional three years. All participants will undergo cognitive assessments and biomarker analyses at the beginning and after the extended intervention period, providing further insights into long-term intervention effects.